"Banking systems in the euro zone and transmission of monetary policy" - José Alejandro Fernández Fernández (Central Bank Review (CBR), 2024)
This study examines the transmission of monetary policy in the eurozone from 2005 to 2021. The novelty of this research lies in defining the European Central Bank's monetary policy through three dimensions extracted via principal component analysis. These components, examined across various neural network models, enable the exploration of the heterogeneity of monetary policy within the Eurozone. Specifically, dimension 2, which represents the yield curve structure and the ECB's interventions in debt markets, serves to categorize the transmission of monetary policy into two groups of countries. The study concludes that variations in banking system characteristics such as margins and leverage, among others, lead to diverse outcomes in the transmission of monetary policy within the credit channel.
Keywords: E51; E52; E58; G21; 330; Monetary policy; Neural networks; Lending margin and credit channel